CALCIUM-ALUMINUM-RICH INCLUSIONS AND AMOEBOID OLIVINE AGGREGATES FROM THE CR CARBONACEOUS CHONDRITES - Aléon J.; McKeegan K.D.; Krot A.N. (My University, 2002)
Calcium-aluminum-rich refractory inclusions (CAIs) in CR chondrites are rare (<1 vol%), fairly small (<500 um) and irregularly-shaped, and most of them are fragmented. Based on the mineralogy and petrography, they can be divided into grossite +/- hibonite-rich, melilite-rich, and pyroxene-anorthite-rich CAIs. Other types of refractory objects include fine-grained spinel-melilite-pyroxene aggregates and amoeboid olivine aggregates (AOAs). Some of the pyroxene-anorthite-rich CAIs have igneous textures, and most melilite-rich CAIs share similarities to both the fluffy and compact type A CAIs found in CV chondrites. One major difference between these CAIs and those in CV, CM, and CO chondrites is that secondary mineral phases are rare. In situ ion microprobe analyses of oxygen-isotopic compositions of 27 CAIs and AOAs from seven CR chondrites demonstrate that most of the CAIs are 16O-rich (delta-17O of hibonite, melilite, spinel, pyroxene, and anorthite < -22%o) and isotopically homogeneous within 3-4%o. Likewise, forsterite, spinel, anorthite, and pyroxene in AOAs have nearly identical, 16O-rich compositions (-24%o < delta-17O < -20 deg). In contrast, objects which show petrographic evidence for extensive melting are not as 16O-rich (delta-17O less than -18%o). Secondary alteration minerals replacing 16O-rich melilite in melilite-rich CAIs plot along the terrestrial fractionation line. Most CR CAIs and AOAs are mineralogically pristine objects that largely escaped thermal metamorphism and secondary alteration processes, which is reflected in their relatively homogeneous 16O-rich compositions. It is likely that these objects (or their precursors) condensed in an 16O-rich gaseous reservoir in the solar nebula. In contrast, several igneous CAIs are not very enriched in 16O, probably as a result of their having melted in the presence of a relatively 16O-poor nebular gas. If the precursors of these CAIs were as 16O-rich as other CR CAIs, this implies either temporal excursions in the isotopic composition of the gas in the CAI-forming regions and/or radial transport of some CAI precursors into an 16O-poor gas. The absence of oxygen isotope heterogeneity in the primary minerals of melilite-rich CAIs containing alteration products suggests that mineralogical alteration in CR chondrites did not affect oxygen-isotopic compositions of their CAIs.